2020
DOI: 10.1093/mnras/staa1892
|View full text |Cite
|
Sign up to set email alerts
|

Gaia white dwarfs within 40 pc – I. Spectroscopic observations of new candidates

Abstract: Abstract We present a spectroscopic survey of 230 white dwarf candidates within 40 pc of the Sun from the William Herschel Telescope and Gran Telescopio Canarias. All candidates were selected from Gaia Data Release 2 (DR2) and in almost all cases had no prior spectroscopic classifications. We find a total of 191 confirmed white dwarfs and 39 main-sequence star contaminants. The majority of stellar remnants in the sample are relatively cool (〈Teff〉 = 6200 K), show… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 88 publications
5
56
1
Order By: Relevance
“…Also reported within the past year, there is a fourth DA star with Balmer emission lines, WD J041246. 85 + 754942.3 (hereafter J0412;Tremblay et al 2020). It is remarkably similar to the three known DAHe stars; it lies in precisely the same and compact region of the HR diagram, and it has rapid rotation.…”
Section: Intrinsic Chromospheric Activity In White Dwarfsmentioning
confidence: 74%
See 1 more Smart Citation
“…Also reported within the past year, there is a fourth DA star with Balmer emission lines, WD J041246. 85 + 754942.3 (hereafter J0412;Tremblay et al 2020). It is remarkably similar to the three known DAHe stars; it lies in precisely the same and compact region of the HR diagram, and it has rapid rotation.…”
Section: Intrinsic Chromospheric Activity In White Dwarfsmentioning
confidence: 74%
“…The exact physical nature of such a spot and its origin remain unclear, despite extensive and multiwavelength efforts to detect a companion, a corona or accretion (Ferrario et al 1997;Weisskopf et al 2007;Wickramasinghe et al 2010). Interestingly, at least two, and possibly three further examples of DAHe stars have been reported within the past year (Gänsicke et al 2020;Reding et al 2020;Tremblay et al 2020); all are isolated (i.e. not cataclysmic variables, no circumstellar discs), relatively fast rotators, and have cool atmospheres where T eff < 10 000 K. Thus, GD 356 is now the prototype of a small class of DAHe stars, but the new discoveries only deepen the mystery.…”
Section: Introductionmentioning
confidence: 99%
“…This highlights the fact that the treatment of the microphysics for cool DB and DBA white dwarfs needs to be revisited. For example, after making a major improvement in the treatment of Stark broadening of neutral helium atoms using computer simulations, Tremblay et al (2020b) also plan to extend their simulations to improve van der Waals broadening.…”
Section: Discussionmentioning
confidence: 99%
“…An issue with the approximate treatment of dereddening in Gentile Fusillo et al (2019a) is unlikely because there is no obvious correlation between the observed offset and distance (Tremblay et al 2019), e.g. the offset is similar even for bright DA white dwarfs within 40 pc (Tremblay et al 2020a) for which reddening is expected to be negligible. It cannot be due to 3D spectroscopic effects, as 1D DB/DBA models predict a similar offset (see Fig.…”
Section: Comparison Between He-and H-atmosphere White Dwarfsmentioning
confidence: 98%
“…Finally, we carry out an additional verification comparing the photometric luminosity of our work with other values published in the literature and also derived photometrically (Kilic et al 2018;Tremblay et al 2020). The results are shown in the bottom right panel of Fig.…”
Section: Methodology and Testingmentioning
confidence: 52%